Bases para un programa de investigación en torno a un modelo didáctico de tipo sistémico e investigativo - Cañal, Pedro; Porlán Ariza, R. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
This paper suggests the need of a model which allows coherent articulation of the different partial contributions in the field of science education. Some implications concerning the characteristics of a research programme on that model are derived.